PERANCANGAN APLIKASI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) PADA PENJUALAN BARANG PRE-ORDER BERBASIS WEBSITE - Rahma Syabania; Neny Rosmawarni (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2021)
The purpose of this research to manage order data online and improve customer service using Customer Relationship Management (CRM) method. Application built programming languange and database mysql. The research method is by direct observation, interviews, and document analysis. System development methods used is Rapid Application Development (RAD). The result of the implementation of the application Customer Relationship Management (CRM) method make it easy for customers to find out what product are being sold and order product quickly. In addition, there is a feature to be able to send notifications to make repayments.